2011
DOI: 10.1371/journal.pone.0022485
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-Cell Death in Response to Pro-Inflammatory Cytokines Is Distinct from Genuine Apoptosis

Abstract: A reduction in functional β-cell mass leads to both major forms of diabetes; pro-inflammatory cytokines, such as interleukin-1beta (IL-1β) and gamma-interferon (γ-IFN), activate signaling pathways that direct pancreatic β-cell death and dysfunction. However, the molecular mechanism of β-cell death in this context is not well understood. In this report, we tested the hypothesis that individual cellular death pathways display characteristic phenotypes that allow them to be distinguished by the precise biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 80 publications
4
57
2
Order By: Relevance
“…It indicated that these metabolic changes are major mediators of oncogenic stress in Bcr-Abl cells. In a report done by Collier et al (2011), using 832/13 and INS-1E rat insulinoma cells, the apoptosis is unlikely to be the primary pathway underlying b-cell death in response to IL-1b + c-IFN (Collier et al, 2011). Results demonstrate that pancreatic b-cells undergo apoptosis in response to camptothecin or staurosporine, but not pro-inflammatory cytokines.…”
Section: Cancer Cellsmentioning
confidence: 82%
“…It indicated that these metabolic changes are major mediators of oncogenic stress in Bcr-Abl cells. In a report done by Collier et al (2011), using 832/13 and INS-1E rat insulinoma cells, the apoptosis is unlikely to be the primary pathway underlying b-cell death in response to IL-1b + c-IFN (Collier et al, 2011). Results demonstrate that pancreatic b-cells undergo apoptosis in response to camptothecin or staurosporine, but not pro-inflammatory cytokines.…”
Section: Cancer Cellsmentioning
confidence: 82%
“…Cell lysis, luciferase assays, and normalization to total protein content were carried out as described previously (27). CCL2 and CCL20 secreted into the media were detected using rat Quantikine (CCL2) or DuoSet (CCL20) ELISA kits from R&D Systems, Inc. (Minneapolis, MN) according to the manufacturer's suggested protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular lysates were harvested using the M-PER Mammalian Protein Extraction Reagent (Thermo Scientific) supplemented with a cocktail of protease and phosphatase inhibitors (Thermo Scientific). Proteins were quantified using a BCA assay (Thermo Scientific), and immunoblotting was performed as previously described (11). Antibodies used for detection of proteins were from the following manufacturers: Santa Cruz Biotechnologies (PO 4-IB␣ and IB␣), Cell Signaling (PO4-Y701 STAT1), and Sigma-Aldrich (␤-actin).…”
mentioning
confidence: 99%